Melanoma: From Incurable Beast to a Curable Bet. The Success of Immunotherapy - Ascierto, Maria Libera; Melero, Ignacio; Ascierto, Paolo Antonio (Frontiers in Oncology, 2015)
After Coley’s observation in 1891 of tumor regression in a patient who developed a postoperative infection, the field of immunotherapy is finally reborn. Avoiding immune destruction is now considered a hallmark of cancer and the immunotherapy arena has exploded with the recent advances demonstrating an improvement in survival and a durability of response in patients with different cancer types which translates into improved overall survival benefit. Here, we provide an overview of the main immune-oncology treatment strategies that, either alone or in combination, are undergoing clinical development. Namely, we will refer to those immunotherapeutic strategies that include adoptive transfer of ex vivo activated T cells, immunomodulatory monoclonal antibodies and cancer vaccines. Our major focus will be to describe these approaches in melanoma, a cancer type transformed by immunotherapy into a potentially curable disease.